2018
DOI: 10.1021/acscatal.8b03066
|View full text |Cite
|
Sign up to set email alerts
|

Electrooxidative Allene Annulations by Mild Cobalt-Catalyzed C–H Activation

Abstract: Versatile cobalt catalysis enabled electrochemical C–H activation with allenes. Thus, allene annulations were accomplished in terms of C–H/N–H functionalizations with excellent levels of chemoselectivity, site selectivity, and regioselectivity under exceedingly mild conditions. Detailed mechanistic studies were conducted, including reactions with isotopically labeled compounds, kinetic investigations, and in-operando infrared spectroscopic studies. Further, computational studies were supportive of a non-rate-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(53 citation statements)
references
References 113 publications
2
51
0
Order By: Relevance
“…Despite the considerable progress in C–H bond functionalization achieved by precious transition metals, there is a continuous interest in developing direct functionalization using abundant 3d late‐transition metals. Owing to the pioneering studies by Kanai, Glorius, and Ackermann, cobalt has emerged as an excellent catalyst for various useful C–H bond functionalizations. Cp*Co III ‐catalyzed linear‐selective C–H alkylation with alkenes has also been developed and demonstrates high regioselectivity and efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the considerable progress in C–H bond functionalization achieved by precious transition metals, there is a continuous interest in developing direct functionalization using abundant 3d late‐transition metals. Owing to the pioneering studies by Kanai, Glorius, and Ackermann, cobalt has emerged as an excellent catalyst for various useful C–H bond functionalizations. Cp*Co III ‐catalyzed linear‐selective C–H alkylation with alkenes has also been developed and demonstrates high regioselectivity and efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…Same year, Ackermann group disclosed electrochemical method to the cyclization of allenes (Scheme ) . This transformation could be carried out using a simple undivided cell under mild conditions without metal precipitation from the cathode.…”
Section: Cyclization Of Alkenesmentioning
confidence: 99%
“…Same year, Ackermann group disclosed electrochemical method to the cyclization of allenes (Scheme 35). [43] This transformation could be carried out using a simple undivided cell under mild conditions without metal precipitation from the cathode. DFT calculation experiments showed that allene insertion was the rate-determining step and was the reason of excellent regioselectivity.…”
Section: Intermolecular Annulation Of Alkenesmentioning
confidence: 99%
“…In as imilar manner,a llenes also participated in the Co-catalyzed annulation reaction with amides to give isoquinolones via electrochemicaloxidation in methanolsolvent. [57] 2.9.4. Dihydroisoquinolones…”
Section: Cationic Isoquinolinesmentioning
confidence: 99%